Personality development among Indigenous youth in Canada: Weaving together universal and community-specific perspectives. (April 2019) - Burack, Jacob A.; Gurr, Erin; Stubbert, Emily; Weva, Vanessa
Abstract: In trying to cobble together a mosaic of information to better understand the disparate and complex issues affecting personality development of the Indigenous youth of Canada, we highlight the need for multiple perspectives. We suggest that pertinent theories from academic psychology, especially those of sociocultural theory and social identity theory, are useful in framing evidence relevant to understanding personality development among Indigenous youth in Canada, but also cite community-specific approaches to understanding and framing issues relevant to personality development within the voice and context of specific communities. The incorporation of Indigenous perspectives in the development of personality constructs would supply an internal cultural view of healthy functioning as opposed to one based only on Western psychological constructs. Moving forward, investigators must apply these language forms and expressions to theories of personality development in a way that expands these theories beyond their non-Indigenous parameters and frameworks. This is a task that must be undertaken with respect for the integrity of the cultures that existed successfully for millenia prior to the European invasion and continue to thrive in the new post-colonial reality.